FORMATION OF THE STRUCTURE OF TOOL STEELS DURING RE-HARDENING (Web of Technology: Multidimensional Research Journal, 2026)
A significant number of works are devoted to various options for heat treatment in order to obtain the required structural parameters of steel and thereby ensure an increase in tool life and an increase in steel wear re-sistance in general. This work proposes two-stage hardening modes for steel types У11, 9ХВГ, ХГС. In this case, the first hardening is performed with heating above Ac3, the second hardening with heating above Ac1. Such heat treatment ensures the production of dispersed secondary car-bides, and the service life of the product increases by 3-4 times. It is shown that a high level of defectiveness of the crystalline structure of hardened steel is achieved only after heating to 1000-1200° C. In this case, the aus-tenite grain grows sharply. Repeated heat treatment using conventional technology ensures not only crushing of the austenite grain, but also inher-itance of an increased level of defectiveness of the crystalline structure. Due to this, wear resistance increases. Increase in wear resistance is possi-ble from 20-25% to 2 times or more. Regularities of formation of optimal structures under conditions of phase recrystallization (when the first is high-temperature) of high-carbon and alloy tool steels, and also, in connec-tion with this, issues of increasing the resistance of cutting and shaping tools of cold deformation. Similar modes of heat treatment (double harden-ing, when the first hardening is high-temperature) can provide an increase in the resistance to crack propagation of steel.